ADMINISTRATIVE COURT JUDGES' EFFORTS TO PROVIDE LEGAL PROTECTION IN ENVIRONMENTAL DISPUTES (Decision Number 59/G/2023/PTUN.JKT) - Muhammad Fathur Rahman; Moh. Fadli; Adi Kusumaningrum (CV. RADJA PUBLIKA, 2025)
The enactment of Law Number 32 of 2009 concerning Management and the Environment has been based on a legal basis and a philosophical basis that has elements of protection for Human Rights. In the provisions of Perma Number 1 of 2023 concerning Guidelines for Adjudicating Environmental Cases, it not only expands the objects of Environmental disputes but also adds a PTUN touchstone in testing the validity of Decisions or Actions taken by Officials/State Administrative Agencies, namely human rights provisions. As the third touchstone, it does not mean that Human Rights Provisions can be set aside in testing environmental disputes. Because environmental disputes are closely related to Human Rights. So that PTUN Judges can classify which Decisions or Actions are classified as violating the Law, AUPB or Human Rights Provisions. This research method is carried out by reviewing literature sources, namely by examining legal principles and norms. This article aims to provide an understanding of Judicial Activism in Environmental cases by the Panel of Judges, which is not impossible based on the Theory of Legal Protection in order to realize the objectives of the law, namely justice, benefit and legal certainty.